Comparison of Onset Age and Pattern of Male Adolescent Smoking in Two Different Socioeconomic Districts of Tehran, Iran - Rezaei, Fatemeh (Medknow Publications & Media Pvt Ltd, 2011)
OBJECTIVES: One of the main strategies to prevent smoking is delaying onset of smoking in adolescents. Thus, identifying the age of smoking and smoking pattern in adolescents gives important knowledge for planning the intervention programs on smoking. METHODS: Students aged 13-15 years old living in the Northern and the Southern Tehran were selected through two separate snowball samplings. In each area six smokers were considered as the seeds and were asked to introduce a smoker friend. The sampling continued until one hundred study subjects were recruited in each area. RESULTS: Although in the area with wealthier socioeconomic status the age at which smoking started was one year more, the number of days of smoking, number of consumed cigarettes, not willingness to quit smoking, ease of access to cigarettes, mother and siblings smoking were more frequent. In contrast, seeing anti-smoking advertisements, father smoking, teachers smoking and education about the adverse effects of smoking were lower than the area with poorer socioeconomic status. CONCLUSIONS: The community level interventions such as not selling cigarettes to juniors, quit smoking help and support, and education of families must be revised. The role of families, through the supervision and control over their children, and parents’ avoidance of smoking should be emphasized.